Expression studies of AOX during adventitious root induction in Olea europaea L. - Macedo, E.S. (2012)
Recently, identification of four alternative oxidase (AOX) gene sequences from olive (Olea europaea L.) has been reported from our group. Three genes could be classified as members of the sub-family AOX1 and one as belonging to the sub-family of AOX2. AOX has been proposed as functional marker candidate for easy-to-root olive genotypes. Validation of AOX as an appropriate marker candidate needs to highlight a close relationship between AOX expression and AOX activity to root induction and/or initiation. Here we present AOX gene expression data during IBA treatments of olive shoot cuttings and the result of studies on the effect of AOX inhibitors and stimulators. Furthermore, variable 3’-UTRs are presented as a source for differential gene regulation in the OeAOX2 gene.